Potential Arrhythmogenic Risk of DDI/DDD Pacing Modes During Atrial Fibrillation - Mugnai, Giacomo; Bertagnolli, Livio; Tomei, Ruggero (Journal of Cardiovascular Medicine and Cardiology, 2014)
In patients with paroxysmal-persistent atrial fibrillation (AF), DDI and DDD pacing modes can be used to assess the clinical burden of AF. This report shows how the DDI mode might trigger ventricular tachyarrhythmias during AF. This potential arrhythmogenic phenomenon should be carefully considered when programming a device in DDI (or DDD) mode in patients with AF.